(untitled) (Research, Society and Development, 2022)
Introduction: Dentistry has stood out on the world stage in the practice of procedures and rehabilitation techniques, aiming at both the health and aesthetics of the individual. In this context, dental prosthesis with implant technology has made significant progress in the last four decades. Advances in surgical techniques have provided improvements in diagnostic methods, implant design and surface quality, as well as a better understanding of the biology of relevant tissues. Thus, the development of new technologies has been subsidizing studies of single surgical steps and placement of prostheses on newly installed implants. Objective: To discuss, through a literature review, the use of the technique of immediate loading on single implants as an alternative treatment for oral rehabilitation. Methodology: Scientific literature searches were carried out in PubMed, Scielo and Google Scholar databases, in the time interval between 2004 and 2022. Discussion and Results: The high stability of the implant immediately after implantation plays an important role in the success rate of the implant, allowing an immediate loading protocol. Conclusion: Immediate loading of individual implants appears to be a highly predictable and very successful treatment modality. However, long-term data are needed to confirm these positive results.